RESPON TIGA VARIETAS CAISIM (Brassica juncea L.) TERHADAP BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR - Destia Susanti Sugeng; Yatmin Yatmin; Priyadi Priyadi (EnviroScienteae, 2019)
Liquid organic fertilizer is a technology in fertilizing to facilitate application. This study aims to study the response of three types of caisim plant varieties that are applied liquid organic fertilizer with several levels of concentration. The study was conducted using a Complete Randomized Block Design (RCBD), which was arranged in factorial with three replications. The first factor is three varieties of caisim (V) consisting of three levels, namely: v1 = tosakan variety, v2 = shinta variety, v3 = kumala variety. The second factor is the concentration of organic liquid fertilizer (C) consisting of three levels, namely: c1 = 3 ml / l water, c2 = 6 ml / l, c3 = 9 ml / l. The homogeneity of the research data was tested by Bartlett test and Tuckey tested the data in addictiveness then analyzed with variance and continued with the smallest significant difference test (LSD) at 5% level. The results showed that the use of three types of caisim varieties showed significant differences in the growth and yield of caisim plants as indicated by the plant height, leaf number and shoot-root ratio. The treatment of liquid organic fertilizer concentration showed no significant difference in the growth and yield of caisim plants in all observed variables.